The Effect of Social Determinants and Socioeconomic Status on Laparoscopic Roux-En-Y Gastric Bypass for Weight Loss: An Analysis of the National Inpatient Sample - Singh, Supreet; Guerra, Jarot J.; Lazar, Paige; Merchant, Aziz M. (The Surgery Journal, 2021)
Objective In the United States, Black and Hispanic patients have a higher prevalence of obesity than Whites (49.6 vs. 44.8 vs. 42.2%, respectively). Despite higher rates of obesity among minority populations, bariatric surgery is performed at higher obesity levels in minorities than in Whites. This study examines the effects of various socioeconomic factors such as race, payer type, and income on the likelihood of undergoing laparoscopic Roux-en-Y gastric bypass (LRYGB) at class II versus class III obesity and their associated complications.Materials and Methods National Inpatient Sample (NIS) from 2016 to 2017 was queried to identify patients at least 18 years of age with a concomitant diagnosis of class II or class III obesity who underwent LRYGB. We analyzed obesity level at the time of LRYGB (class II vs. class III), postoperative intestinal obstruction during the admission, and occurrence of any noninfectious complication related to the surgery as our main outcomes. A multivariate logistic regression model was utilized to assess the association between our outcomes and socioeconomic factors associated with the admission.Results A total of 76,405 LRYGB operations were included. Out of this total, 83% (63,640) LRYGB operations were in class III obesity. Black patients had a lower rate (11.6%) of LRYGB procedures at class II obesity than White (17.6%) and Hispanic (18%) patients (p < 0.001). Medicare, Medicaid, and lower income quartiles also showed lower rates of operation at class II obesity (p < 0.001). Black patients were 29% (95% confidence interval [CI]: 0.61–0.83, p < 0.001) less likely than Whites to have a LRYGB procedure at class II obesity, they were 119% (95% CI: 1.17–4.11, p = 0.0014) more likely to suffer a postoperative intestinal obstruction, and they were 93% (95% CI: 1.31–2.84, p < 0.001) more likely to suffer a noninfectious complication.Conclusion Socioeconomic disparities in the surgical management of severe obesity persist in the United States, especially for LRYGB. This study highlights multiple demographic factors that led to LRYGB at later obesity levels. Black patients were also more likely to be associated with postoperative complications during the admission. The determinants of health disparities in obese patients need to be examined further to reduce potential long-term morbidity and mortality in minorities. Further research is also required to identify the adverse effects of health disparities in patients with severe obesity and obesity-related comorbidities.
Keywords: bariatric surgery; surgical outcomes; health services research; obesity treatment; health disparities; laparoscopic Roux-en-Y gastric bypass